Kelayakan Usaha dan Prospek Penjualan Furniture Mahoni (Swietenia mahagoni) di Sentra Pengerajin Furniture Mahoni Desa Wringinpitu Kabupaten Jombang - Aisah Windiani Aisah; Dyah Ayu Sri Hartanti; Miftachul Chusnah; Siti Nur Qomariyah (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
This study aims to determine the business feasibility and sales prospects of mahogany furniture in terms of the R/C ratio of furniture craftsmen in Wringinpitu Village, Jombang Regency. The location of this research was carried out purposively (purposive sampling) and was carried out from February to March 2022. The data collection technique used in data collection was primary data sourced from direct interviews with mahogany furniture craftsmen using a questionnaire. Data analysis used in this study is the analysis of costs, revenues, revenues, and the ratio of R/C. The results of sales in Wringinpitu Village in 2021 within a year average Rp. 129,825,000, every month the income of craftsmen has increased and decreased due to a decrease in the amount of raw materials, and a decrease in consumer purchasing power for furniture. The results of the analysis show that the total income from the prospect of selling mahogany furniture in Wringinpitu Village within one year is an average of Rp. 41,671,045. This shows that the mahogany furniture craft business in 2021 is good enough to run. The results of the feasibility analysis of the R/C/Ratio show that the prospect of selling mahogany furniture in Wringinpitu Village is 1.5, the result of the R/C ratio shows that it is feasible to work on. This can be seen from the total revenue with a total cost that is greater than one, which is 1.5 ˃ 1. The B/C Ratio analysis shows that the sales prospects for mahogany furniture are 0.5, the value of the B/C Ratio shows that < 1 then the business is not feasible to develop.